Clinical utility of far-infrared therapy for improvement of vascular access blood flow and pain control in hemodialysis patients - Soo Jeong Choi; Eun Hee Cho; Hye Min Jo; Changwook Min; Young Sok Ji; Moo Yong Park; Jin Kuk Kim; Seung Duk Hwang (The Korean Society of Nephrology, 2016)
Background: Maintenance of a well-functioning vascular access and minimal needling pain are important goals for achieving adequate dialysis and improving the quality of life in hemodialysis (HD) patients. Far-infrared (FIR) therapy may improve endothelial function and increase access blood flow (Qa) and patency in HD patients. The aim of this study was to evaluate effects of FIR therapy on Qa and patency, and needling pain in HD patients. Methods: This prospective clinical trial enrolled 25 outpatients who maintained HD with arteriovenous fistula. The other 25 patients were matched as control with age, sex, and diabetes. FIR therapy was administered for 40 minutes during HD 3 times/wk and continued for 12 months. The Qa was measured by the ultrasound dilution method, whereas pain was measured by a numeric rating scale at baseline, then once per month. Results: One patient was transferred to another facility, and 7 patients stopped FIR therapy because of an increased body temperature and discomfort. FIR therapy improved the needling pain score from 4 to 2 after 1 year. FIR therapy increased the Qa by 3 months and maintained this change until 1 year, whereas control patients showed the decrease in Qa. The 1-year unassisted patency with FIR therapy was not significantly different from control. Conclusion: FIR therapy improved needling pain. Although FIR therapy improved Qa, the unassisted patency was not different compared with the control. A larger and multicenter study is needed to evaluate the effect of FIR therapy.